Nucleation mechanisms in a SiO2-Li2O-P2O5-ZrO2 biomedical glass-ceramic: Insights on crystallisation, residual glasses and Zr4+ structural environment. Issue 4 (April 2022) - Cicconi, M.R.; Belli, R.; Brehl, M.; Lubauer, J.; Hayakawa, T.; Kimura, K.; Hirota, T.; Usui, K.; Kohara, S.; Onodera, Y.; Lohbauer, U.; Hayashi, K.; et al.
Highlights: We reverse-engineered a Zr-rich multicomponent Li-silicate glass having SiO2 /Li2 O < 2. Residual glasses representing different stages provide a unique point of view. AXS shows that zirconia (sub)-nanoclusters are present at the nucleation stage. The critical toughness was increased by adjusting the nucleation parameters. Amorphous Li-enriched μ-areas induce the nucleation of Li2 SiO3 . Abstract: In manufacturing reliable glass-ceramics, bulk chemistry and appropriate thermal treatments are critical points. To better understand the influence of nucleation parameters on the crystallisation behaviour and mechanical properties of multicomponent glass-ceramics, we studied the effects of time and temperature on phase stabilisation, the evolution of the crystal phases and physical properties of a Zr-rich lithium-silicate having a SiO2 /Li2 O molar ratio < 2. Here, we also provide insights into the structural environment of Zr 4+ at the early stage of nucleation by Anomalous X-ray Scattering (AXS). By reverse-engineering a commercial material through remelting and sequential thermal treatments, we observed the strong effect of the nucleation temperature on the final mineral assemblage and of the volume fractions of the lithium-disilicate phase on the fracture toughness ( KIc ). Indeed, the KIc value was increased from ∼0.8 MPa.m ½ in the pristine glass up to ∼ 2 MPa.m ½, if compared to the original commercial material exhibiting a KIc value of 1.6 MPa.m ½ . Furthermore, the synthesis of residual glasses at different stages of the thermal treatments allowed us to observe the changes in the glass network structure and properties. AXS was used to extract the contribution exclusively coming from Zr for different nucleation steps. The differential pair distribution functions Δ Z r g ( r ) show two distinct peaks at ∼2.10 Å and 3.44 Å, respectively associated with Zr-O and Zr-Zr/Zr-Si correlations with the formation of edge sharing in addition to corner sharing polyhedra. It was discerned the occurrence of (sub)nano-sized clusters enriched in Zr. These local clusters do not show changes during the different thermal treatments, either for higher temperatures or longer times. No Zr phases are stabilised in the crystallised materials, suggesting that these clusters do not evolve above the critical nucleus size. All evidence points to a highly heterogeneous environment and the coexistence of three structural regions i) (sub)nano Zr-clusters, ii) P enriched μ-areas, iii) residual silicate glass. The evolution and spatial distribution of these units influence the final properties.